Pengaruh Unsur-Unsur Customer Experience terhadap Minat Pembelian Kembali (Studi Kasus pada Konsumen Anomali Coffee Ubud) - UPAYANI, NI KADEK AYU LILIS; SUSRUSA, KETUT BUDI; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
The Influence of Customer Experience on Customer Repurchase Intention (A Case Study on Anomali Coffee Ubud Customers) Coffee shop is one of the culinary business which is growing significantly enough. The Anomaly Coffee is a coffee shop which is located at Jalan Raya Ubud No. 88, Ubud, Bali it prepares different types of coffee and foods as the other coffee shops do. Anomali Coffee it also prepares several supporting facilities which can contribute to the customer experience.Its interior design is unique and provides free wifi. Apart from that, the consumers are provided with the opportunity to brew own coffee. This current study was intended to identify and analyze the influence of the elements of customer experience to repurchase intention.The samples in the current study were taken using the accidental sampling technique.The respondents totaled 60. The data were analyzed using the multiple linear regression method.From the result of the study, it could be concluded that the customer experience could be categorized as good. Based on the result of the partial test, the variables of sense and the relate variable have a significant influence on repurchase intention. Simultaneously, the elements of customer experience which consist of the sense, feel, think, act and relate have a significant influence on repurchase intention at Anomali Coffee customer. The R-square score obtained was 78.8%; the rest was obtained from the other factors which were not investigated in the current study.